Five traditional Chinese medicine formulations for addressing COVID-19 - Zhang, Junyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Covid-19 has spread worldwide, with its initial outbreak occurring in China. The Chinese government employed not only Western medicine but also traditional Chinese medicine (TCM) in their response. TCM, due to its potential to enhance human immunity, was considered a valuable tool in prevention. Furthermore, the analysis of TCM recipes has shed light on their efficacy. Some of the five recipes, including LHQW, XFBD and LCDD, have been found to have the capacity to enhance the patients’ immunity responses. Furthermore, specific formulations like LHQW, XFBD, and HSBD have the capability to disrupt the attachment of COVID-19 to host cells by impeding its interaction with the ACE2 receptor. It is worth noting that Western medicine (WM) has limitations, thus, leading to the exploration of a combined approach involving both TCM and WM. Clinical observations have demonstrated that the treatment combining TCM and WM is more effective compared to treatments with either approach isolation. However, further research is needed to identify more favorable treatment strategies.